UPAYA MENINGKATKAN HASIL BELAJAR SISWA SMK PADA MATERI LOGIKA MATEMATIKA DENGAN MENGGUNAKAN PENDEKATAN KONTEKSTUAL - Asrita Septiani; Martin Bernard; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study is a action research.  This study aims to see the improvement of student learning outcomes in mathematical logic material trough a contextual approach to class XI at SMK TI Garuda Nusantara Cimahi. This research was conducted in the academic year 2021-2022 with 15 students in this study. Data collection techniques were carried out by means of observation, documentation and using test questions. The instrument that will be given to students is 5 test questions carried out in 2 cycles. The first cycle will carry out a pretest which means doing an initial test and a posttest which means a final test for students by being given an understanding of mathematical logic material using a contextual approach. Based on the results of the research that has been carried out, the following results were obtained:  1) learning outcomes in the initial test get a score of 7 students with an average (46.67%), 2) learning outcomes in the final test get an increase of 13 students with an average (86 ,66%), seen from this study most of the student learning outcomes have met the criteria for the KKM score. From the results of this study, it can be concluded that through acontextual approach can have a positive influence on learning outcomes carried out on  in mathematical logic.